MEETING ON A BRIDGE: OPPOSING WHITENESS IN SOCIAL WORK EDUCATION AND PRACTICE - Khan, Maryam; Absolon, Kathy (Canadian Social Work Review / Revue canadienne de service social, 2021)
Challenging Whiteness and its dominance in social work education and practice is an act of resistance with violent repercussions for Indigenous and racialized social work educators who do this work. In this paper, two authors—one Indigenous and one racialized settler—discuss building bridges between mainstream social work and Indigenous-centred social work by sharing their reflexive lived experiences (personal and professional) of decentring Whiteness, engaging in decolonization, and deploying wholistic ways of teaching and being at a faculty of social work located on Turtle Island. The authors end by sharing some possible strategies and discussion points which can work to bridge the gap and challenge Whiteness in social work.